Pendampingan Sertifikasi Halal Umkm Sektor Makanan dan Minuman di Desa Panempan Pamekasan - Ardyansyah, Farid; Ijabah, Nur; Amaliya, Najmi Maulita; Jannah, Anisatul; Alfia, Nanda (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Halal certification is a crucial component in the food and beverage industry, particularly for Micro, Small, and Medium Enterprises (MSMEs) within this sector. Certification influences the formulation and ingredients of food items, consequently enhancing customer awareness of products that adhere to food and halal standards. The Halal Information System (SIHALAL) is a platform intended to optimise the halal certification process for MSME food and beverage enterprises. MSME participants in the region continue to have challenges in accessing and inputting data into the SIHALAL portal. This community service program aims to enhance the comprehension of MSMEs in Panempan Village about the assistance offered by MSME stakeholders in the halal certification registration process via the SIHALAL application. The methodology used include interviews and direct observation, including multiple phases: issue identification, planning, and execution. This community service program resulted in support for halal certification and the identification of halal items to enhance MSMEs' awareness in Panempan Village on the significance of acquiring halal certificates in the food industry. Support services for NIB registration and halal certification use the SIHALAL application. Two MSMEs achieved halal certification with the SIHALAL application throughout the certification process.